Treatment and outcomes for indigenous and non‐indigenous lung cancer patients in the Top End of the Northern Territory. Issue 7 (18th July 2021) - Basnayake, Thilini L.; Valery, Patricia C.; Carson, Philip; De Ieso, Paolo B.
Abstract: Background: Lung cancer is the most common cause of cancer‐related mortality for both Indigenous and non‐Indigenous Australians, and the death rate of lung cancer in Indigenous Australians is increasing. Aims: To provide a comprehensive description of patterns of lung cancer presentation, diagnosis, treatment and outcomes in Indigenous and non‐Indigenous Australians in the Top End of the Northern Territory. Methods: Retrospective cohort study of adult patients with a new diagnosis of lung cancer in the Top End between January 2010 and December 2014. Unadjusted survival probabilities by indigenous status were calculated. The primary end‐point was all‐cause mortality. Results: Despite receiving similar diagnostic procedures and treatment, Indigenous Australians with lung cancer have poorer 1‐ and 5‐year survival (25.0% and 9.4% respectively), when compared to non‐Indigenous Australians included in the study (42.0% and 16.2% respectively). Indigenous lung cancer patients were more likely to be female (51.6% of indigenous patients were female, compared to 30.5% non‐indigenous), be current smokers (61.3% vs 36.9%), have more comorbidities (73.6% vs 52.7%, 24.2% vs 5.3% and 30.8% vs 14.2% for respiratory disease, renal insufficiency and diabetes mellitus respectively), and live in more socio‐economically disadvantaged (66.7% vs 14.2%) and very remote areas (66.1% vs 6.8%). They were also more likely to die at home, compared to their non‐indigenous counterparts (64.3% vs 26.7%). Conclusions: Indigenous patients from the Top End diagnosed with lung cancer were more likely to have poorer survival outcomes when compared to non‐indigenous people. Potential reasons for the discrepancy in survival need to be addressed urgently.